ANALISA PENDAPATAN USAHA TANI APEL (Malus Sylvester Mill) DI KABUPATEN PASURUAN (Studi Kasus Desa Andonosari Kecamatan Tutur Kabupaten Pasuruan) - Ilmiatul Imama; Novi Itsna Hidayati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
Apple (Malus Sylvester Mill) is an annual fruit plant which is one of the horticultural commodities in the sub-tropics or high land which has very good prospects to be developed now and in the future. Andonosari Village, Tutur Subdistrict, Pasuruan Regency is the largest apple orchard in Indonesia. The purpose of this study is to be able to analyze the costs incurred, analyze the income to be received and analyze the level of value of efficiency of apple farming in Andonosari Village, Tutur District, Pasuruan Regency. The method used in this study is descriptive regression. The main reason researchers used this method was because they wanted to know the existence of income, expenditure and efficiency in growing apple plants in Andonosari Village, Tutur Sub-District, Pasuruan Regency. The results of the research proved that apple farming carried out during the harvest season was still profitable to implement. Apple farming can be said to be not good, if it is proven that so far farmers have not utilized production inputs maximally to increase production. R / C ratio greater than one shows that apple farming in Andonosari Village is currently feasible to cultivate. The conclusion of the study is that the R / C ratio shows that apple farmers get> 1, meaning that apple farming is classified as efficient and profitable. This can be proven that the R / C ratio is the cost incurred in Manalagi apples 3. The suggestions given by the author are (1) Farmers should be able to improve the farms currently managed. (2) Farmers must understand more about farming costs and know things that are found in apples. (3) To increase selling prices, farmers are expected to be able to improve the quality of fruit, especially in uniformity in size